Encyclopedia of Genetics, Genomics, Proteomics, and Informatics - Rédei, George P. (Springer Netherlands : Imprint: Springer, 2008)
The new, 3rd edition is an updated version of the best-seller earlier books. It includes about 56% more words than the 1,392-page 2nd edition of 2003. The number of illustrations increased to almost 2,000 and their quality has improved by design and four colors. Cross-references among entries are expanded. The statements are supported by references; more than 14,000 journal papers and more than 3,000 books are listed. The book includes ~1,800 current databases and web servers. Retractions and corrigenda are pointed out. It covers the basics and the latest in genomics, proteomics, genetic engineering, small RNAs, transcription factories, chromosome territories, stem cells, genetic networks, epigenetics, prions, hereditary diseases, patents, etc. Similar integrated information is not available in textbooks or on the Internet. The journal reviews called it the best, high-quality resource for researchers, instructors and students of basic and applied biology, as well as for physicians and lawyers or even for interested laymen because of the clarity of presentation.